Pengaruh Corporate Governance, Ukuran Perusahaan dan Profitabilitas Terhadap Tax Avoidance - Islah Amara; Emmiliana Hartanti (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of corporate governance, company size and profitability on tax avoidance. In this study the sample used was manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018 with a total sample of 67 companies with a purposive sampling technique. This study uses multiple regression with a common effect approach. Tests conducted in this study are descriptive statistical tests, normality tests, multiple regression analysis tests, coefficient of determination tests, and partial significant tests. The results of this study indicate that company size and profitability have no effect on tax management, while corporate governance has an effect on tax avoidance.